Analisa Kepuasan Pelanggan terhadap Kualitas Pelayanan pada PT Tj Bros dengan Metode SERVQUAL (Service Quality) - Dionisius Hardin; Nur Nawaningtyas (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to evaluate the service quality of PT TJ Bros using the SERVQUAL method, which includes five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Data were collected through a Likert-scale questionnaire from 50 active customers selected using purposive sampling. The analysis measured the gap between customer expectations and their perceptions of the company's services.The findings indicate that all service dimensions exhibit negative gaps, meaning the service quality does not fully meet customer expectations. The responsiveness dimension shows the largest gap (-0.80), reflecting delays in responding to customer complaints or requests. The tangibility dimension also demonstrates a gap (-0.40), indicating a need for improvements in physical facilities, such as cleanliness, waiting area comfort, and employee appearance. In the empathy dimension, customers feel a lack of personalized attention, with a gap of -0.60.To enhance customer satisfaction, the company is recommended to improve its customer response system using technology-based complaint management, upgrade physical facilities, and train employees in communication and personalized service. Adjustments to employee uniforms and training to maintain service consistency are also suggested.In conclusion, comprehensive improvements in operational systems, facilities, and employee skills are necessary to enhance service quality. By meeting or exceeding customer expectations, PT TJ Bros can boost customer loyalty and strengthen its competitive position in the market.